Exploring adolescents' experiences of continuing to wear face masks during COVID‐19: A qualitative descriptive study in Barcelona (Spain) - Mariela Aguayo‐González; Juan M. Leyva‐Moral; David Giménez‐Diez; Andreu Colom‐Cadena; Isabel Martínez; Carolina Watson; Anna Bordas; Cinta Folch; Jordi Casabona (Wiley, 2024)
Abstract Background The COVID‐19 pandemic prompted the use of face masks as a social distancing measure. Although evidence supports their effectiveness in preventing infection, it remains unclear why some adolescents choose to continue wearing them postpandemic, even when it is no longer mandatory. This study aims to explore adolescents' experiences of wearing face masks during the COVID‐19 pandemic when their use was no longer mandatory. Method In this exploratory qualitative study, data were collected from 16 adolescents through face‐to‐face semistructured interviews. The participants were asked about the reasons and feelings associated with continuing to wear masks, as well as the contexts in which they felt safe without a mask. The collected data were analysed using Braun and Clarke's thematic analysis. Results Three main themes were identified: (1) Navigating complex decision‐making: balancing safety and self‐image, (2) peer influence dynamics and (3) managing the future: weather dynamics and pandemic evolution. Discussion The potential implications of withdrawing COVID‐19 preventive measures, such as mask‐wearing, beyond the pandemic remain understudied. It is crucial to further investigate the perceptions related to wearing masks and its cessation, especially amongst vulnerable individuals. Patient or Public Contribution Due to methodological constraints associated with participants' age, they were not engaged in the design, data analysis, data interpretation or manuscript preparation phases of the study.